Near-infrared and highly photostable squaraine-based nanoparticles for photoacoustic imaging guided photothermal therapy. (March 2023) - Rong, Xiang; Xia, Xiang; Wang, Ran; Su, Zehou; Liu, Ting; Zhang, Zongwei; Long, Saran; Du, Jianjun; Fan, Jiangli; Sun, Wen; Peng, Xiaojun
Abstract: Effective photothermal agents (PTAs) are of particular importance for anticancer phototherapy. Nevertheless, conventional PTAs are frequently plagued by inadequate photostability, short-wavelength absorption, and low photothermal conversion efficiency (PCE). Herein, we designed and synthesized a near-infrared squaraine dye (SQ) with the maximum absorption wavelength at ∼710 nm. The squaraine dye demonstrates much enhanced photostability compared with indocyanine green (ICG), a commercial PTA. To improve the tumor targeting capacity, SQ was encapsulated into polymeric nanoparticles (SQ-NPs), which show a high photothermal conversion of 52.8% with strong photoacoustic signals upon 760 nm NIR laser irradiation. Through intravenous injection into tumor-bearing mice, SQ-NPs accumulate at the tumor site and efficiently inhibit the growth of tumor under photoacoustic image-guided photothermal therapy. Highlights: A near infrared squaraine dye (SQ) is synthesized with high photostability and high photothermal conversion efficiency. The dye SQ was encapsulated into polymeric nanoparticles with good biocompatibility and tumor targeting ability. SQ nanoparticles can inhibit tumor growth via photoacoustic image-guided photothermal therapy.